Características del cuidador familiar del niño con discapacidad intelectual: una revisión integradora - García-Morán, Gretel Alexandra (Universidad de Sonora, 2022)
The family caregiver, intrinsic unit of the context of children with intellectual disabilities, who require help to perform various activities, because due to their condition makes it impossible for them to perform them by themselves, demanding care and supervision. Objective: To describe the main characteristics of the family caregiver of a child with intellectual disabilities. Methodology: A literature search was carried out in PUBMED, LILACS and Scielo databases, considering articles ≤ 10 years old, in English, Spanish and Portuguese, using the descriptors "family caregiver", "intellectual disability", "child", "informal caregiver" and the Boolean operator "AND". A total of 494 articles were located, 474 were excluded because they did not meet the inclusion criteria. There were 20 articles for the analysis of titles and abstracts; after critical reading and discrimination of information, only 7 were analyzed for the present review. Results: Main caregivers: mothers and fathers of children with intellectual disabilities, age between 35 to 40 years, from middle to low social classes, most common level of education completed high school, caregivers were mainly housewives; caregivers experience depression, anxiety and stress, some use religious coping style. Caregiving overload and quality of life in caregivers depends on the severity of the child's disability, and whether or not they send them to special institutions. Conclusions: Family functioning should be considered to develop interventions to support caregivers' quality of life, health professionals should address family empowerment to decrease caregiving overload and increase quality of life.